Effect of left ventricular assist device on the hemodynamics of a patient-specific left heart. - Kannojiya, Vikas; Das, Arup Kumar; Das, Prasanta Kumar (Medical & Biological Engineering & Computing, 2022)
This article describes the numerical efforts made to investigate the influence of a left ventricular assist device (LVAD) on the patient-specific left heart's hemodynamics. Two different computational geometries with left heart have been simulated over the entire cardiac cycle (case 1: healthy heart without LVAD and case 2: diseased heart with LVAD). The blood flow was simulated by implementing Bird-Carreau non-Newtonian model. Simulation results show that implantation of LVAD pump imparts major influence on the hemodynamics of the heart; it also provides a cardiac output of 4.87 L/min even at the diastolic phase. Furthermore, post LVAD implantation, approximately eight times more wall shear stress, is noticed at the aorta during the ventricular systole. In particular, major changes in the fluidics are observed inside the aortic region. A possibility of flow stagnation is noticed near the aortic root during the diastolic phase due to the bisection of incoming bloodstreams from the outflow graft. The flow characteristics of the LVAD pump are also observed to be significantly different from the idealized simulations (idealized tubular inlet situation). The observation of this study can help in understanding post-implant critical hemodynamic issues due to pump performance and its subsequent impact on the heart. A simulation approach-based study has been performed to investigate the influence of LVAD on the hemodynamics of a heart. A 3D computational model of a patient-specific heart has been created from CT scan datasets for diastole and systole phases (a). An axial flow blood pump has been implanted computationally into the left heart (b). The implanted blood pump enhances the cardiac output and elevates shear generation (c) and (d).